Nomogram for Predicting Bone Development State of Female Children and Adolescents–A Fast Screening Approach Based on Pubes Stages for Growth and Development - Yang, Ruoyu; Wang, Liyan; Wu, Chao; Song, Haihan; Hu, Jingyun; Jing, Chen; Zhang, Qiaolin; Jia, Shihao; Lin, Xunyi; Liu, Yang; Cai, Ming; Yan, Xu; et al. (Frontiers in Pediatrics, 2021)
Objective: To develop a nomogram for predicting bone development state (BDS) of female children and adolescents in a large scale. Methods: 447 female students were designated as the training cohort to develop the predictive model, while 196 female students were used as the validation cohort to verify the established model. Bone age, height, body mass, body fat percentage and secondary sexual characteristics were recorded, and BDS was determined with the chronological age and bone age. Multivariate logistic regression was conducted to determine the factors, and nomogram was developed and validated with the training and validation cohorts, respectively. Results: 147 female students were identified as BDS abnormal in the training cohort (32.9%), and 104 were determined in the validation cohort (53.1%). Age, height, weight and pubes stage were selected for the predicting model. A nomogram was developed and showed a good estimation, with a C-index of 0.78 and a good calibration in the training cohort. Application of the nomogram to the validation cohort showed a similar C-index of 0.75 and a good calibration. Conclusion: A nomogram for predicting bone development was developed, which can provide a relatively good estimation of BDS for female children and adolescents in Chinese metropolis.